The Effect Of Accountability In The Management And Optimization Of The Use Of Village Funds On The Development Of BUMG - Nazira Ulfa; Hayatur Rahmi; Ismi Laina; Tirahmah; Rahmawati (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the influence of accountability and optimization of village fund utilization on the development of BUMG (Badan Usaha Milik Gampong) in Cot Unou Village, Kuala Subdistrict, Bireuen Regency. The research employed a descriptive quantitative approach with data collected through questionnaires and interviews from 85 respondents, consisting of village officials and community members. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results show that accountability in management significantly affects BUMG development, as indicated by t-count > t-table (6.695 > 1.994) and a significance level of 0.007 < 0.05. Similarly, the optimization of village fund utilization has a significant impact, with t-count > t-table (6.272 > 1.994) and significance level of 0.000 < 0.05. Simultaneously, both variables jointly have a significant effect on BUMG development, proven by F-count 498.622 > F-table 3.11 and significance value of 0.000 < 0.05. The correlation coefficient (R) of 0.961 indicates a very strong relationship, while the coefficient of determination (R²) of 0.924 shows that 92.4% of BUMG development is explained by the two independent variables, and the remaining 7.6% is influenced by other factors outside this research model.